“Stereoelectronic Deprotection of Nitrogen”: Recovering Nucleophilicity with a Conformational Change - Gazizov, Almir S.; Smolobochkin, Andrey V.; Rizbayeva, Tanzilya S.; Vatsadze, Sergey Z.; Burilov, Alexander R.; Sinyashin, Oleg G.; Alabugin, Igor V. (Journal of organic chemistry, 2023)
Ureas are often thought of as “double amides” due to the obvious structural similarity of these functional groups. The main structural feature of an amide is its planarity, which is responsible for the conjugation between the nitrogen atom and carbonyl moiety and the decrease of amide nucleophilicity. Consequently, since amides are poor nucleophiles, ureas are often thought of as poor nucleophiles as well. Herein, we demonstrate that ureas can be distinctly different from amides. These differences can be amplified by rotation around one of the ureas’ C–N bonds, which switches off the amide resonance and recovers the nucleophilicity of one of the nitrogen atoms. This conformational change can be further facilitated by the judicious introduction of steric bulk to disfavor the planar conformation. This change in reactivity is an example of “stereoelectronic deprotection,” a concept when the desired reactivity of a functional group is produced by a conformational change rather than a chemical modification. This concept may be used complementarily to the traditional protecting groups. We also demonstrate both the viability and the utility of this concept by the synthesis of unusual 2-oxoimidazolium salts possessing quaternary nitrogen atoms at the urea moiety.